Perancangan Pengendalian Kecepatan Motor Induksi Tiga Fasa Pada Mesin Sentrifugal Dengan Pendekatan Model Viteckova Orde Dua Menggunakan Metode Hybridfuzzy-SMC - ahmad faizal (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2018)
Induction motor has a weakness in the speed settings, the speed will change when there is a change in load or control signal disturbance, it takes a controller that is able to overcome the shortcomings of the induction motor, one of the controller is fuzzy. Fuzzy controllers have the advantage of modeling a complex non-linear function. But fuzzy controllers have weaknesses in the form of overshoot and system oscillation. One of the controllers that is able to overcome the weakness of overshoot and oscillation of the system from the fuzzy controller is the Sliding Mode Control (SMC) controller. SMC has the advantage of being robust and able to work on non-linear system systems that have model or parameter uncertainty. Based on simulation results from fuzzy hybrid controller and SMC able to cover the weakness of fuzzy and robust controller in overcoming the load and disturbance changes. Proven with time response analysis on overshoot and steady state error better than fuzzy controller with longer transient time value at maximum load with steady state error 0,0085 Rpm with Maximum overshoot 0,38% and without system oscillation.